Effects of task complexity or rate of motor imagery on motor learning in healthy young adults - Nargis Heena (Wiley, 2021)
Abstract Background A growing body of evidence suggests the benefit of motor imagery in motor learning. While some studies tried to look at the effect of isolated mental practice, others evaluated the combined effect of motor imagery and physical practice in clinical rehabilitation. This study aimed to investigate the effects of task complexity or rates of motor imagery on motor learning in health young adults. Methods Eighty‐eight healthy individuals participated in this study. Participants were randomly allocated to either Group A (50% complex, N = 22), Group B (75% complex, N = 22), Group C (50% simple, N = 22), or Group D (75% simple, N = 22). Participants in the complex groups performed their task with nondominant hand and those in simple groups with a dominant hand. All participants performed a task that involved reach, grasp, and release tasks. The performance of the four groups was examined in the acquisition and retention phase. The main outcome measure was the movement time. Results There were significant differences between immediate (i.e., acquisition) and late (i.e., retention) movement times at all three stages of task (i.e., MT1 [reaching time], MT2 [target transport time], and TMT [reaching time plus object transport time]) when individuals performed complex task with 75% imagery rate (p < .05). Similarly, there were significant differences between immediate and late movement times at all stages of task except the MT2 when individuals performed simple task with 75% imagery rate (p < .05). There were significant effects of task complexity (simple vs. complex tasks) on immediate movement time at the first stage of task (i.e., MT1) and late movement times of all three stages of task (p < .05). There were significant effects of the rate of imagery (50% vs. 75%) on late movement times at all three stages of tasks (p > .05). Additionally, there were no interaction effects of either task complexity or rate of imagery on both immediate and late movement times at all three stages of tasks (p > .05). Conclusion This study supports the use of higher rates (75%) of motor imagery to improve motor learning. Additionally, the practice of a complex task demonstrated better motor learning in healthy young adults. Future longitudinal studies should validate these results in different patient's population such as stroke, spinal cord injury, and Parkinson's disease.